A sacred command of reason? Deceit, deception, and dishonesty in nurse education - Rolfe, Gary (Nursing philosophy, 2016)
Kant (Grounding for the Metaphysics of Morals. Hackett, Indianapolis, 1797) described honesty as ‘a sacred command of reason’ which should be obeyed at all times and at any cost. This study inquires into the practice of dishonesty, deception, and deceit by universities in the UK in the pursuit of quality indicators such as league table positions, Research Excellence Framework (REF) scores, and student satisfaction survey results. Deception occurs when the metrics which inform these tables and surveys are manipulated to suggest an improvement in quality when, in fact, the raised scores are merely the result of clever strategic planning. Deceit occurs when these manipulated scores are deliberately and knowingly presented as real improvements in research and educational quality. It might be argued that, within the context of the artificial ivory tower world of academe, this is a game played by almost every academic in every higher education institution with no real losers and little wider consequence. However, this study suggests that some of the strategies employed by institutions to improve their scores without directly addressing the issue of quality can, in certain practice-based disciplines such as nursing, result in dire consequences for practitioners and service users. It concludes with a number of suggestions taken from personal experience to resolve the tension between the contractual demands placed on nurse academics by their employers and the moral and practical obligations of their professional body, most notably the use of subversion. The conclusion, contra Kant, is that the most effective strategy against dishonesty and deception is often more dishonesty and deception.